Rewiring the Mind: How Faith and Biology Interact in Personal Transformation - Insights from Bruce Lipton’s Biology of Belief - Siti Khadijah Binte Mahfuh; Dodi S. Truna (Yayasan Dar Arrisyah Indonesia, 2025)
This study explores the intricate relationship between Islamic faith and biological processes in shaping personal transformation. Drawing upon both spiritual principles and modern neuroscience, it investigates how core Islamic practices—such as Sabr (patience), Tawakkul (trust in Allah), and Dhikr (remembrance of Allah)—influence cognitive and emotional well-being. In parallel, the research incorporates insights from Bruce Lipton's